2012
DOI: 10.1523/jneurosci.5227-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissociation within the Entorhinal Cortex for Memory Retrieval of an Association between Temporally Discontiguous Stimuli

Abstract: Anatomical connectivity and single neuron coding suggest a segregation of information representation within lateral (LEC) and medial (MEC) portions of the entorhinal cortex, a brain region serving as the primary input/output of the hippocampus and maintaining widespread connections to many association cortices. The present study aimed to expand this idea by examining whether these two subregions differentially contribute to memory retrieval for an association between temporally discontiguous stimuli. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 38 publications
(50 reference statements)
7
68
0
Order By: Relevance
“…There were no significant group differences: group, F(2, 16) = 0.216, p = 0.808; Session 3 Group interaction, F(12, 96) = 0.700, p = 0.748; therefore, the data from these groups were collapsed into a single ''control'' group. Notably, even after 7 days of acquisition sessions, CR% in most rats did not reach the previously reported asymptote for trace eyeblink conditioning with a regular 500-ms trace interval in rats ($60%; Weiss et al, 1999;Beylin et al, 2001;Morrissey et al, 2012). These results suggest that extending the trace interval by 250 ms effectively weakened the animal's ability to associate the CS and US.…”
Section: Increasing Prefrontal Neuron Activity Enabled Learning Acrosmentioning
confidence: 57%
See 1 more Smart Citation
“…There were no significant group differences: group, F(2, 16) = 0.216, p = 0.808; Session 3 Group interaction, F(12, 96) = 0.700, p = 0.748; therefore, the data from these groups were collapsed into a single ''control'' group. Notably, even after 7 days of acquisition sessions, CR% in most rats did not reach the previously reported asymptote for trace eyeblink conditioning with a regular 500-ms trace interval in rats ($60%; Weiss et al, 1999;Beylin et al, 2001;Morrissey et al, 2012). These results suggest that extending the trace interval by 250 ms effectively weakened the animal's ability to associate the CS and US.…”
Section: Increasing Prefrontal Neuron Activity Enabled Learning Acrosmentioning
confidence: 57%
“…CR acquisition requires a larger number of CS-US pairings as the duration of the trace interval becomes longer (Weiss et al, 1999). The longest interval over which learning typically can take place in rats is 500 ms (Beylin et al, 2001;Morrissey et al, 2012;Takehara et al, 2003), at which interval CR acquisition is impaired by the inactivation of the prelimbic region (Takehara-Nishiuchi et al, 2005). To detect enhancement of learning by our manipulation, we extended the trace interval to 750 ms ( Figure 2A).…”
Section: Increasing Prefrontal Neuron Activity Enabled Learning Acrosmentioning
confidence: 99%
“…Consistent with this finding, following neurotoxic lesions encompassing much of the EC in rats, rats showed a selective impairment in the acquisition of trace fear but not delay fear conditioning (Esclassan et al 2009). In addition, although one study reported no effect on trace eyeblink conditioning after electrolytic lesions of lateral EC (LEC) prior to training (Suter et al 2013), reversible inactivation of the LEC area after training with the area intact did impair tone recall (Morrissey et al 2012). Taken together, lesion studies indicate that temporal associative learning depends on the integrity of the EC.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningmentioning
confidence: 99%
“…Our research shows that against a backdrop of increased beta amyloid immunoreactivity in the cortex and hippocampus, there are replicable effects of feeding cholesterol on learning and memory. Given the essential role of the cortex and hippocampus in the acquisition and recall of trace conditioning in both eyelid and heart conditioning [26, 39, 55, 134138], it is tempting to draw causal inferences from the accumulation of beta amyloid in those structures and the observed changes in learning and memory particularly given our findings of cholesterol-induced changes in the membrane properties of hippocampal neurons [123]. In fact, this recapitulates the inferences the field continues to make concerning beta amyloid and Alzheimer's disease.…”
Section: Effect Of Cholesterol and Copper On Beta Amyloid Accumulmentioning
confidence: 99%